Integrated Islamic Education in Brunei Darussalam: The Hopes and Challenges - Lubis, Maimun Aqsha; Wekke, Ismail Suardi (EDUCARE, 2009)
ABSTRACT: This study is a qualitative research into the implementation of integrated Islamic education in Brunei Darussalam. The Pioneer Schools (Sekolah Rintis) and the Thoughtful School (Sekolah Hatiminda) are solid evidence that Brunei has decided to settle on the integrated Islamic education for its future generations. Some problems surface later which are thought to impede a fully successful implementation of the integrated Islamic education in the country. This work aims to examine the extent of the implementation of the integrated Islamic education system and to evaluate whether there is an evident need to revise the current system. This research has identified, however, the needs to look into the implementation of three main solutions to successfully accomplish the vision of assimilating the integrated Islamic education system in the country in the light of (1) the implementation of the Thoughtful Schooling system; and (2) the Educatorâs capability to prepare and practice a good lesson plan, according to the âEight Steps of the Teaching Learning Processâ in the class room.KEY WORDS: integrated Islamic education on teaching and learning, and its hopes and challenges in Brunei Darussalam educational context.Â Â About the Authors: Dr. Maimun Aqsha Lubis is a Senior Lecturer at the Department of Educational Methodology and Practices, Faculty of Education UKM (National University of Malaysia); and Ismail Suardi Wekke is a Postgraduate Student for Ford Foundation International Fellowship Program in UKM (National University of Malaysia). They could be reached at: mal@ukm.my and iswekke@gmail.com Â How to cite this article? Lubis, Maimun Aqsha & Ismail Suardi Wekke. (2009). âIntegrated Islamic Education in Brunei Darussalam: The Hopes and Challengesâ in EDUCARE: International Journal for Educational Studies, Vol.1(2) February, pp.141-156. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 9, 2008); Revised (January 19, 2009); and Published (February 17, 2009).